SAT0078 Prospective Observational Study To Evaluate The Use of Musculoskeletal Ultrasonography To Improve Rheumatoid Arthritis Management: Canadian Experience (ECHO). (15th July 2016) - Stein, M.; Rampakakis, E.; Sampalis, J.S.; Bensen, W.
Abstract : Background: Musculoskeletal Ultrasound (MSUS) has been shown to be superior to clinical examination in the detection of synovitis in patients with Rheumatoid Arthritis (RA), and can be used to improve diagnostic accuracy [1] and potentially monitor disease changes in order to make treatment decisions aimed at optimizing patient care. Since the creation of the Canadian Rheumatology Ultrasonography Society (CRUS) in 2010, an increasing number of rheumatologists has been trained in the use of MSUS. Objectives: The overall study objective is to compare the effectiveness of MSUS to Routine Care (RC) as a disease management tool in patients with moderate-to-severe RA for whom a change in treatment is indicated. The study also assessed the predictive power of US assessments. Methods: Descriptive interim analysis of the "Echo" study, a prospective two-cohort, quasi-experimental study of patients diagnosed with active moderate-to-severe RA managed either with MSUS or as per RC. In order to be eligible for the study patients must require a change in treatment as per the judgment of the treating physician. Patients are followed for 1 year with assessments at baseline, 3, 6, 9, and 12 months. Outcome measures of interest include CDAI Remission, DAS-28 Remission and DAS-28 Low Disease Activity (LDAS). Results: A total of 339 patients (70.1% female) with a mean (SD) age of 58.7 (11.79) years and disease duration of 7.4 (10.2) years were enrolled, without any significant differences between treatment groups. There were no differences between the two treatment groups with respect to the study outcomes. However, higher total US Erosion Scores at baseline were associated with lower rates of LDAS at 9 months (OR =0.810; P=0.047) and 12 months (OR =0.808; P=0.078) and lower rates of DAS-28 Remission at 9 months (OR =0.811; P=0.60); higher total synovitis GREY scale at baseline was associated with a lower rate of LDAS at 6 months (OR =0.913; P=0.014) and DAS – 28 Remission at 3 months (OR =0.911; P=0.074) Conclusions: MSUS assessments can be useful predictors of future disease remission in patients with RA. The impact of MSUS on disease management and clinical outcomes requires further study. References: Colebatch AN et al. Ann Rheum Dis 2013, 72:804–814. Disclosure of Interest: None declared